Improvement Of Employee Competency Through the Learning Duty Program and Self-Learning Permits - Dadan Wahyudi; Euis Salbiah; Irma Purnamasari (Universitas Djuanda, 2019)
In improving the quality of the State Civil Apparatus (ASN) or Civil Servants (PNS) in accordance with the development of science and technology in this milineal era, employees are required to be able to develop in accordance with the needs of organizations that are also developing, so that the quality of the human resources highly highlighted, based on the Head of the State Personnel Agency Regulation No. 8 of 2013 Technical Competency is the ability of every Civil Servants (PNS) that includes knowledge, skills and work attitudes that are needed in carrying out his job duties. The Directorate General of Conservation of Natural Resources and Ecosystems is one part of the Ministry of Environment and Forestry which aims to improve the quality of the Ministry's Human Resources. Thus an increase in competency among employees within the Directorate General of Natural Resources and Ecosystem Conservation covers the dimensions of Skills, Knowledge, Self-Concepts, Character and Encouragement through the study assignment program and independent study permit, which in increasing this competency can provide increased competency of employees in carry out their duties in accordance with their positions, where employees are more adept at responding, careful, fast and intelligent in carrying out their duties in accordance with applicable regulations when employees carry out tasks within the scope of the Directorate General of Conservation of Natural Resources and Ecosystems.